Review on postharvest quality and handling of apple - Anbesse Girma Shewa; Daniel Alemu Gobena; Mikiyas Kebede Ali (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Apple is a climacteric temperate fruit with high market demand providing essential components to the body. Nowadays, apple production is increasing every year especially in EU member countries are the highest producer. Hence, this paper reviews the postharvest quality and associated changes during handling. Usually, farmers face difficulty in estimating the right harvesting time though Different methods exist to test the maturity stage such as counting the days after full bloom, color change, firmness test, measuring soluble sugar, starch iodine test and Streif index. Depending on different factors, farmers can choose the best maturity estimation method in various locations. Postharvest diseases of apples makeup a major part of the economic losses incurred during apple production. Annual losses of many fruits, including apple, vary from 5 to 35% and for developing countries, it ranges between 20%-50%. The most common causes are poor harvesting methods, transportation and storage methods which can open access for fungal growth species such as Botrytis species. B. cinerea is one of the most important of the species with unique characteristics causing the highest losses.